2019
DOI: 10.1007/s12195-019-00602-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell Communication Network Factor 4 (CCN4/WISP1) Shifts Melanoma Cells from a Fragile Proliferative State to a Resilient Metastatic State

Abstract: While deregulated intracellular signaling initiates melanoma, intercellular crosstalk within the tumor microenvironment, often coordinated by soluble factors, is essential for melanoma progression and metastasis. One such secreted matricellular protein, cellular communication network factor 4 (CCN4/WISP1), stimulates metastasis in other malignancies. Here, we report that CCN4 expression is associated progressively with reduced overall survival in patients with primary melanomas. To reveal the roles of CCN4 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The single cell suspensions were aliquoted among three antibody panels to characterize the tumor infiltrating lymphocytes by flow cytometry (see Figures S4-S6 for gating strategies). While the B16F0 and YUMM1.7 KO variants were generated using a double nickase CRISPR/Cas9 approach, similar results were obtained using a homology directed repair strategy (34,51). Additional controls for puromycin selection of CRIPSR/Cas9 edited cells using B16F0 cells transfected with a pBabe-puromycin retrovirus also behaved functionally similar in vitro and in vivo as wild-type B16F0 cells (34).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The single cell suspensions were aliquoted among three antibody panels to characterize the tumor infiltrating lymphocytes by flow cytometry (see Figures S4-S6 for gating strategies). While the B16F0 and YUMM1.7 KO variants were generated using a double nickase CRISPR/Cas9 approach, similar results were obtained using a homology directed repair strategy (34,51). Additional controls for puromycin selection of CRIPSR/Cas9 edited cells using B16F0 cells transfected with a pBabe-puromycin retrovirus also behaved functionally similar in vitro and in vivo as wild-type B16F0 cells (34).…”
Section: Resultsmentioning
confidence: 89%
“…To illustrate the approach, we focused on Cell Communication Network factor 4 (CCN4/WISP1), as it is upregulated in invasive breast cancer (Klinke, 2014) and correlates with a lower overall survival in patients diagnosed with primary melanoma (Deng et al, 2019). Functionally, CCN4 promotes metastasis in melanoma by promoting a process similar to the epithelial-mesenchymal transition (Deng et al, 2019(Deng et al, , 2020.…”
mentioning
confidence: 99%
“…Recent literature connects the epithelial-mesenchymal transition (EMT) with tumor immune escape (20, 28, 29). We previously found that CCN4 activates EMT-associated genes in melanoma cells thus increasing metastatic potential (11, 12). Motivated by encouraging clinical correlates, we report that melanoma-derived CCN4 also stimulated tumor-induced immunosuppression in mice, particularly by directly suppressing antigen-induced IFN γ release by CD8 + T cells and by expanding and recruiting G-MDSC.…”
Section: Discussionmentioning
confidence: 99%
“…CCN4-knockout (CCN4-KO) B16F0 and YUMM1.7 cells were generated using a double nickase-based CRISPR/Cas9 approach as previously described (11). Additionally, for the B16F0 model, DNMT3A- and CCN4-knockout cells were obtained through transfection with a mix of CRISPR/Cas9 KO and Homology-Directed Repair (HDR) plasmids, followed by puromycin selection (12). A control cell, B16F0-Ctr, was also created using a pBabe-puro retrovirus (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation